Study on The Implementation of Differentiated Learning in The Kurikulum Merdeka for Biology Instruction at SMAN 1 Sendana - M, Nanda Adrian; L, Hamka; Patongai, Dian Dwi Putri Ulan Sari; P, Muhiddin (Biology Teaching and Learning, 2025)
Abstract. This study aims to analyze the implementation of differentiated learning within the Kurikulum Merdeka in Biology subjects at SMAN 1 Sendana. The research employs a descriptive qualitative approach using observation, semi-structured interviews, and documentation techniques. The theoretical framework refers to Carol Ann Tomlinson’s concept of Differentiated Instruction, which emphasizes the adaptation of content, process, and product of learning based on students’ readiness, interests, and learning profiles. The findings indicate that Biology teachers have implemented differentiated learning through diagnostic assessments, curriculum analysis, and strategies for differentiating content, process, and product. Evaluation is carried out continuously using both formative and summative approaches. Although the delivery of material has not been fully adjusted to students’ levels of learning readiness, differentiated learning is effectively implemented and fosters an inclusive, student-centered learning environment. These findings provide practical contributions for Biology teachers and other schools in designing adaptive learning aligned with the principles of Kurikulum Merdeka, as well as serving as a reference for developing instructional strategies that are responsive to student diversity.Keywords:  Differentiated instruction, Independent Curriculum, Biology, Diagnostic assessment, Teaching strategy